Application of a Thermodynamic Database to Predict the Phases and Microstructure of Pt-Al-Cr-Ru Alloys. (2015) - Cornish, L.A.; Süss, R.; Motha, S.; Ukpong, A.M.; Shongwe, M.B.; Witcomb, M.J.; Chown, L.H.; Watson, A.
Abstract: Pt-based alloys with analogous structures to Ni-based alloys are being developed for high temperature applications in aggressive environments. The alloys require a high volume fraction of ∼Pt3 Al precipitates (L12 phase) for optimum microstructure and performance. Work has been done on the optimisation of the microstructure of Pt-Al-Cr-Ru alloys. In this study, phases and phase proportions of Pt-based quaternary alloys were calculated as a function of temperature using Thermo-Calc and Pandat software with the developmental Pt-Al-Cr-Ru database. The calculated results were compared with the corresponding experimental microstructures. The proportions of the eutectic at solidification were estimated from the calculated equilibrium graphs, and also from Scheil simulation calculations. Most of the calculated equilibrium phase proportion graphs showed that the primary phase was (Pt), which agreed with the experimental findings. The calculations also showed that with decreasing temperature, the ∼Pt3 Al volume fraction increased to a maximum, which was just under 0.8 at ∼1000 °C for Pt81.5 :Al11.5 :Cr4.5 :Ru2.5 . To assess the heat treated samples, the calculated phase proportions were determined at 1100 °C. The proportion of ∼Pt3 Al increased after heat treatment at 1100 °C, although the maximum proportion was often calculated to occur at slightly lower temperatures.